2015
DOI: 10.4314/jab.v89i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing yield and profitability of cassava in the savannah and forest zones of Democratic Republic of Congo through intercropping with groundnut

Abstract: Objective: This study was conducted to simulate intercropping of cassava and groundnut as practiced by farmers in the savannah and forest zones of Democratic Republic of Congo (DRC). It aims to (i) evaluate the intercropping of two most cultivated food crops (Cassava and Groundnut) under conditions of marginal soils of the tropics and (ii) propose alternatives to farmers that can enhance productivity. Methods and results: At each location, a split plot design was used with Cassava branching habit (branching ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…NAROCAS1 had the highest positive response to profit (1% level of significance) and similarly planting NASE19 and NASE14 significantly improves profit implying that planting the varieties results in an increment in profit. Results from this study are in agreement with studies by Ndonda et al (2015) who observed that the choice of cassava variety determines profitability of a cropping system. Ndonda et al (2015) further found low efficiency associated with local cassava variety and concluded that improved varieties that are more productive and increase the net income and thus provide an economic benefit.…”
Section: Profit Functionsupporting
confidence: 92%
See 2 more Smart Citations
“…NAROCAS1 had the highest positive response to profit (1% level of significance) and similarly planting NASE19 and NASE14 significantly improves profit implying that planting the varieties results in an increment in profit. Results from this study are in agreement with studies by Ndonda et al (2015) who observed that the choice of cassava variety determines profitability of a cropping system. Ndonda et al (2015) further found low efficiency associated with local cassava variety and concluded that improved varieties that are more productive and increase the net income and thus provide an economic benefit.…”
Section: Profit Functionsupporting
confidence: 92%
“…Results from this study are in agreement with studies by Ndonda et al (2015) who observed that the choice of cassava variety determines profitability of a cropping system. Ndonda et al (2015) further found low efficiency associated with local cassava variety and concluded that improved varieties that are more productive and increase the net income and thus provide an economic benefit. Again this confirms (Itam et al, 2018) that improved cassava varieties are more profitable.…”
Section: Profit Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…The soils are mainly clay‐sandy in Mvuazi and sandy in Litoy. 9 Data on laboratory analyses conducted at the soil and water facilities at the University of Kisangani (UNIKIS) in Tshopo province and the Kongo University (KU) in Kongo Central province in DR Congo are summarized in Table 2 . In the savanna zones, soils are characterized by low fertility.…”
Section: Methodsmentioning
confidence: 99%
“…This result indicates a benefit of using intercropping compared to sole cropping in terms of land use efficiency. Previous studies on cassava groundnut intercropping have ping over sole cropping in cassava-groundnut-based intercropping systems [16] and [17].…”
Section: Land Use Efficiencymentioning
confidence: 99%